Detection of honey adulteration with C3, C4, and CAM sugar syrups using Laser-Induced Breakdown Spectroscopy - Abog, Jeremiah A. (College of Home Economics, University of the Philippines Diliman, 2023)
This study explored the use of laser-induced breakdown spectroscopy (LIBS) as a rapid authenticity screening method for Philippine honey. The LIBS method and logistic regression modeling were conducted on pure honey from Apis mellifera and pure adulterant syrups such as coconut sap, agave, rice, beet sugar, and fructooligosaccharide syrups. Results show that out of the 12 identified elements in pure honey and pure adulterant syrups, the major elements (>0.4 wt%) were Si, Cu, Fe, Ti, C, Mg, Al, Ba, and Cr, the minor element (0.1–0.4 wt%) was Ca, and the trace elements (<0.1 wt%) were Be and Li. Univariate analysis of pure honey and pure adulterant syrups using an unpaired t-test with Welch's Correction revealed significant differences in Ca, Mg, and Si values. Multivariate analysis using glm and stepAIC functions for variable selection revealed that C, Fe, and Mg were the ideal key predictor variables in the model to differentiate adulterated and pure honey samples. The initial model produced test error estimates of 0.1310-0.01314 and an accuracy of 86.86-86.89%, which was improved using Ca-Mg-Si variables, yielding test error estimates of 0.0928-0.0929 and an accuracy range of 90.70-90.71%. However, the C-Fe-Mg variables produced a more superior predictive model with test error estimates of 0.0860-0.0861 and an accuracy range of 91.39-91.40%. This study concluded the application of C, Fe, and Mg variables in predicting honey adulterations with C3, C4, and CAM sugar syrups.